Atrial septal aneurysm in adult patients: spectrum of clinical, echocardiographic presentation and to propose a new classification on the basis of trans-thoracic-two-dimensional echocardiography - Jatav, Rajendra Kumar; Kumbhare, Mamta B.; Surender, T.; Rachan, Ch.; Krishna, T. V. Vamshi (International Journal of Research in Medical Sciences, 2017)
An atrial septal aneurysm is a rare but well recognized cardiac abnormality of uncertain clinical relevance. ASA is definitively associated with congenital and acquired heart diseases but also can be presented as an isolated and totally asymptomatic entity. On the basis of our TTE finding we are proposing a new classification of ASA. We have classified ASA in to two major types: (A) Localized, and (B) Generalized. Both major types are further Sub-classified into 5 possible types on the basis of movements of ASA. New classification of ASA is as follows (1) A/B Type 1R: if the bulging is in the RA only (2) A/B Type 2L: if the bulging is in the LA only (3) A / B Type 3RL : if the major excursion bulges to the RA and lesser excursion bulges toward LA (4) A/B Type 4LR: if the maximal excursion of the atrial septal aneurysm is toward the LA with a lesser excursion toward the RA (5) A / B Type 5: if the atrial septal aneurysm movement is bidirectional and equidistant to both atria during the cardiorespiratory cycle. We found higher prevalence (2.24%) of ASA. A/B Type 2L and A/B Type 4LR were most common types. All type of ASA had particular clinical and echocardiographic characteristics. Mobile ASA and ASA with >10 mm excursion are associated with a higher risk of stroke.